A systematic review of the nature and correlates of sleep disturbance in early psychosis. (February 2017) - Davies, Gabriel; Haddock, Gillian; Yung, Alison R.; Mulligan, Lee D.; Kyle, Simon D.
Summary: Sleep disturbances are common in people with a diagnosis of schizophrenia and have been associated with increased symptom severity, neurocognitive deficits and reduced quality of life. Despite a significant body of literature in this field, there has been limited investigation of sleep disturbance in the early course of the illness. This systematic review aims to synthesise and evaluate the available data exploring sleep in early psychosis, with two key research questions: 1) What is the nature of sleep disturbance in early psychosis? and 2) What are the correlates of sleep disturbance in early psychosis? From an initial search, 16, 675 papers were identified, of which 21 met inclusion/exclusion criteria. The preliminary evidence suggests that self-reported sleep disturbances are prevalent in early psychosis and may be associated with symptom severity, as well as elevated rates of both help-seeking and suicidality. Abnormalities in sleep architecture and sleep spindles are also commonly observed and may correlate with symptom severity and neurocognitive deficits. However, due to significant methodological limitations and considerable heterogeneity across studies, evidence to support the reliability of these associations is limited. We outline a research agenda, emphasising the prospective use of gold-standard sleep measurement to investigate the prevalence and nature of sleep disturbances in early psychosis, as well as how these may be related to the onset and persistence of psychotic symptoms.